A STUDY OF THE CURRENT STATE, DESIRABLE STATE AND NEED ANALYSIS FOR APPROACHES FOR DEVELOPING LEARNING MANAGEMENT COMPETENCY OF TEACHERS OF NONTHABURI SCHOOL CLUSTER 2 - Suphanthong, Tuenta; Charoenkul, Nantarat (Journal of Educational Review Faculty of Education in MCU, 2022)
The purpose of this research was to study the priority need of the approaches for Developing Learning Management Competency of Teachers of Nonthaburi School Cluster 2. The population were Nonthaburi School Cluster 2. This study was descriptive research. There were 64 informants. Administrators were the school director, deputy directors, assistant directors, 8 heads of subjects. The research instruments were rating-scaled questionnaires and rating-scaled appropriability and possibility evaluation forms. The data were analyzed by frequency distribution, percentage, mean, standard deviation, PN Imodified and mode. The results were as follows. 1) the current state of the approaches for Developing Learning Management Competency of Teachers of Nonthaburi School Cluster 2, overall, was at the moderate level, with the highest mean on using and development of innovative media technology for learning management. As for the desirable state of the approaches for Developing Learning Management Competency of Teachers of Nonthaburi School Cluster 2, overall, was at the high level, with the highest mean on using and development of innovative media technology for learning management. 2) The first priority needs index was Knowledge and competence in learning design; the second priority needs index was learning management that is student-centered; and the last priority needs index was measurement and evaluation.